TRAINING AND IMPROVING YOUNG KICKBOXERS IN COMBINATION TECHNIQUES (International Scientific Journal Alfraganus, 2024)
In this thesis, conclusions are presented on the methodology of training young kickboxers incombination methods and its improvement, as well as experimental justification of itseffectiveness, research results are presented, and relevant practical recommendations arehighlighted.
Keywords: indicator, technical-tactical, kickboxing, quickness, strike